Maternal near miss and maternal mortality in a tertiary care centre of North Karnataka: a retrospective study - Lokapur, Jyoti G.; Antaratani, Ramalingappa C.; Lokapur, Mallikarjun G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Maternal near-miss cases and maternal deaths serve as crucial indicators of obstetric care quality. Analysis of these cases in tertiary care settings provides valuable insights for improving maternal healthcare services. Objective of this study was to analyze the prevalence, causes, and outcomes of maternal near-miss cases and maternal deaths in a tertiary care center in North Karnataka. Methods: This retrospective observational study was conducted at Karnataka Medical College and Research Institute, Hubli, during 2023. The study population comprised all pregnant women who were admitted to the Department of Obstetrics and Gynecology at KMCRI during 2023. The identification and classification of maternal near-miss cases were conducted in accordance with the Ministry of Health and Family Welfare (MoHFW), Government of India guidelines. Data was collected from multiple hospital records and analyzed using SPSS version 22. Results: Among 11,658 live births, 113 maternal near-miss cases and 51 maternal deaths were recorded (maternal mortality ratio: 437.46 per 100,000 live births). The majority of cases occurred in the 20-25 years age group (near-miss: 43.4%, deaths: 54.9%). Primigravidae constituted 48.7% of near-miss cases and 43.1% of deaths. Most cases were referrals (near-miss: 76.1%, deaths: 70.6%) and booked outside the institution (near-miss: 94.7%, deaths: 82.4%). Hypertensive disorders were the leading cause of near-miss events (65.5%), and maternal deaths were also primarily attributed to hypertensive complications (31.4%), acute kidney injury (23.5%), and sepsis (19.6%). Mechanical ventilation was required in 90.2% of maternal deaths and 53.1% of near-miss cases. Conclusions: The high proportion of referred cases and unstable presentations emphasizes the need to strengthen peripheral healthcare facilities and referral systems. Early recognition of complications, timely referral, and improved antenatal care at primary healthcare levels are crucial for reducing maternal morbidity and mortality.